The Influence of Zinco on Bone Repair: A Literature Review - Souza, Karen G. de [UNESP]; Santos, Pamela L. dos; Marques, Rodrigo F. C. [UNESP]; Jafelicci, Miguel [UNESP]; Santos, Felipe A. dos [UNESP]; Magdalena, Aroldo G. [UNESP] (Brazilian Chemical Soc, 2018)
The challenge in the treatment of bone defects, increased the search for an ideal material, which promotes, more quickly, the regeneration of the bone tissue. Obviously the ideal material does not exist, what has characteristics closer is the autogenous bone, but still has restrictions as the quantity acquired. Due to these shortcomings new materials are being developed. The biomaterials containing zinc in their structure were highlighted for a better repair of the injured bone. The present study analyzed the influence of zinc on bone repair, according to a review study and concluded that the element zinc is fundamental in the protein synthesis of several enzymes that have indirect binding to bone repair. The action of zinc is to stimulate the synthesis of proteins and consequent action on the enzymes / hormones related to bone growth. In addition, zinc is an inhibitory agent of osteoclast cells, which are related to bone resorption.
Keywords: Zinc; Biomaterials; bone formation